Editorial: Do clinical services need to take conduct disorder more seriously?. (20th August 2013) - Coghill, David
<x xml:space="preserve">Abstract</x> Oppositional defiant disorder (ODD) and conduct disorder are common disorders and frequent reasons for referral to child and adolescent mental health services (CAMHS). Figures from epidemiological studies in the US suggest that around 10% of children suffer from ODD and similar numbers from CD. Data from the UK estimates that around 6% of children and young people aged 5 to 16 years have a clinically diagnosed conduct disorder in England, with much higher rates in males than females.